(untitled) (Eurasian Journal of Ecology, 2016)
The studies found that the frequency distribution of individual alleles and genotypes, there are significant differences depending on the species and of the strain, and spread from the area of specialization of the breed. A similar situation was noted structurally genes responsible for the expression of a particular protein fraction of milk.